Development and Implementation of a Microcontroller-Based Smart Modular Aquaponic System for Sustainable Food Production - Abdulkadir, Abubakar; Abdurrahman, Mubarak; Mutalib, Yusuf Ova; Hamidat, B. Y.; Hamza, Jamilu Bala (Darul Yasin Al Sys, 2025)
Aquaponics integrates aquaculture and hydroponics into a symbiotic, soil-free agricultural system that offers a sustainable solution to global food production challenges. In response to the increasing demand for environmentally sustainable and resource-efficient farming methods, this study presents the development and implementation of a microcontroller-based smart modular aquaponic system aimed at automating water quality regulation, with a focus on pH level control. Traditional aquaponic systems rely heavily on manual monitoring and adjustment of critical parameters, often leading to inefficiencies and inconsistencies. The proposed system integrates a pH sensor with a microcontroller that triggers a pumping mechanism to adjust water conditions when pH levels exceed 7.1. Experimental validation across three monitoring intervals (08:00, 14:00, and 20:00) demonstrated the system’s ability to maintain pH within the optimal range of 6.8–7.1. The findings confirm that the automated approach significantly improves operational stability, enhances water resource efficiency, and promotes environmental sustainability within aquaponic systems. Moreover, the modular configuration facilitates scalability and customization across diverse settings. This study underscores the transformative potential of automation in advancing aquaponics as a viable model for sustainable and technologically integrated food production.